Some Novel Anticonvulsant Agents Derived from Phthalazinedione - Zayed, M. F.; Ayyad, R. R. (Arzneimittelforschung, 2012)
A series of phthalazinedione bearing substituted oxadiazole moiety derivatives X(1–7) were synthesized in good yield and evaluated for their possible anticonvulsant activity. The structures of the synthesized compounds were confirmed on the basis of their spectral data and elemental analysis. Their anticonvulsant activities were evaluated by the maximal electroshock induced seizure (MES) and subcutaneous pentylenetetrazole (PTZ) tests. All the tested compounds showed considerable anticonvulsant activities in at least one of the anticonvulsant tests. Moreover, some of the tested compounds exhibited moderate anticonvulsant activities in both MES and PTZ tests. From these results,[3-)2-Alkoxycarbonylmethylthioxadiozol-5-yl)methyl -6-Iodophthalazine – 1,4- (2H,3H)-1,4-dion] (X1–7) derivatives could be recommended as novel structures of broad spectrum anticonvulsants.
Keywords: antiepleptics; phthalazinedione; 1, 3, 4-oxadiazole